Effects of negative workplace behavior on job insecurity and turnover intention in healthcare workers: roles of psychological resilience - Zou, Jie; Yang, Yanhong; Chen, Ling; Bi, Yin; Li, Na; Luo, Qin; Zhang, Jin (Frontiers in Public Health, 2025)
IntroductionAlthough negative workplace behavior as a key factor in healthcare staff turnover intention was well established, the mechanisms by which negative workplace behavior affects turnover intention are unclear. Extending the affective event theory, we aimed to (a) identify the interrelationships between negative workplace behavior, job insecurity, psychological resilience, and turnover intention in the healthcare setting and (b) clarify the mechanism among these variables.MethodsA cross-sectional survey was conducted in China from February to April 2023 utilizing a quota sampling method. The Chinese version of the negative behaviors in health care survey, the workplace insecurity scale, the 10-item Connor-Davidson Resilience Scale, and the turnover intention scale were used to investigate.ResultsThe survey resulted in 1,180 valid responses. Results were consistent with our hypothesized framework in which healthcare workers' turnover intention was significantly and positively influenced by negative workplace behavior (β = 0.251, p < 0.01) and job insecurity (β = 0.322, p < 0.01). Job insecurity partly mediated the association between negative workplace behavior and turnover intention, which were significantly moderated by psychological resilience (β = −0.041, p < 0.05).ConclusionsNegative workplace behavior is critical in turnover intention among healthcare workers. One important consideration for hospital administrators and health policymakers is creating a peaceful and harmonious workplace to reduce the risk of unfavorable workplace conduct and turnover intention toward healthcare personnel. An essential psychological resilience-improving program should be developed to reduce the damage of negative workplace behavior and job insecurity against healthcare workers.